Pelatihan MOL Bonggol Pisang (Musa Paradisiaca) sebagai Dekomposer untuk Pengomposan Sampah Residu pada Pekerja di TPS3R Baratan, Kabupaten Jember - Luthfiyah, Lenny; Nafiah, Faranindita Khosyyatun; Puspita, Hachi Ayu; Rahmadhani, Faras Jingga (AKSILAR: Akselerasi Luaran Pengabdian Masyarakat, 2025)
This community service aims to empower workers at the Reuse, Reduce, Recycle Waste Processing Site (TPS3R located in Baratan Village, Arjasa District, Jember Regency) by utilizing residual waste into organic fertilizer through the production of Local Microorganisms (MOL) from banana stems. The methods used are counseling, demonstration of methods, and mentoring. The results of the activity show that TPS3R Baratan workers are able to produce MOL from banana stems independently using easily obtained materials such as banana stems, rice washing water, and palm sugar. Banana stems contain nutrients and decomposing microbes such as Bacillus sp., Aeromonas sp., and Aspergillus niger which are effective in decomposing residual waste. The use of MOL from banana stems as a solution to reduce residual waste accumulation is expected to increase the independence of TPS3R Baratan workers and support sustainable waste management.